Prematurity at birth and increased cardiovascular risk: is a metabolomic approach the right solution? - Pier Paolo Bassareo; Vassilios Fanos; Claudio Barbanti; Giuseppe Mercuro (Hygeia Press di Corridori Marinella, 2013)
In recent decades, steady progress in the field of physiopathology and the use of increasingly sophisticated technological procedures have resulted in an increase in the survival rates of babies born preterm. However, some of these individuals, although surviving, may at times be faced with severe consequences. Some conditions may be manifested at an early age (particularly dysmorphisms as well as neurological and ophthalmological conditions), whilst others (namely renal and cardiovascular events), evolve gradually and are manifested only years later. In a number of reports in literature it has been demonstrated how prematurity and consequent low weight at birth are risk factors for developing hypercholesterolemia, arterial hypertension, obesity, type 2 diabetes, QTc interval prolongation at basal electrocardiogram, early endothelial dysfunction, structural and functional cardiac modifications, and increased death rates from coronary heart disease. Even some drugs used in the neonatal management of preterm babies may have a detrimental effect on their future cardiac function. The aim of this narrative review was to overview the up to know few reports about metabolomics (a new and promising technique which allows the systematic study of the complete set of metabolites in a biological sample) applied to the identification of a possible future cardiovascular system involvement in subjects born preterm. An outlook of the requirements for future researches has been also discussed.